The Communication Strategy in Resourced-Based Waste Segregation in Klungkung Subdistrict, Klungkung Regency: - - Ida Bagus Putra Adnyana; I Nengah Lestawi; I Wayan Wastawa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
Increasing the number of human population, consumerism, and changes in modern activities directly proportional with the number amount of waste. As a tourist destination, Klungkung Regency occupies the second position as the largest waste producer in the Province of Bali and there are still 3,795.83 tons or 11.09% of unmanaged waste to total waste production in Klungkung Regency. Resourced-based waste management is the earliest or upstream handling of household waste which is the key to the success of the next steps. This study aims to analyze: (1) Communication pattern are implemented to change people's behavior; (2) Inhibiting factors of communication strategy; (3) Implications of communication strategy that applicated by local goverment. This study uses a descriptive research method with a qualitative approach. The research location is in Klungkung District, Klungkung Regency with a focus on Semarapura Kangin Village. Data collection was carried out through observation, interviews, and documentation studies. The theory used as the basis for the analysis is: (1) Persuasive Communication Theory; (2) Attitude Change Theory, (3) Social Judgement Theory; and (4) Diffusion of Innovations Theory. The findings in this study are: (1) The pattern of communication in the implementation of Tri Hita Karana uses group communication, while in the implementation of laws and regulations it uses patterns of interpersonal communication, group communication, and mass communication; (2) There are 3 (three) factors inhibiting communication, namely technical barriers (limited communication media used), semantic barriers (regional language) and human barriers (perception and time of visit); (3) The implications of a persuasive communication strategy consist of 3 (three) dimensions, namely cognitive, affective, and conative in the form of: increasing public awareness about the negative impacts of waste and the importance of waste segregation, changing attitudes, and changing behavior in sorting waste and becoming a customer of a waste bank. Strict application of real sanctions is needed for people who violate laws and regulations related to waste management and waste segregation according to the types listed in laws and regulations. The local government of Semarapura Kangin is expected to innovate more in reusing waste that is still economically valuable, reuse and recycle organic and inorganic waste through various methods involving the active role of the community, such as: optimizing the use of Waste Recycling Holes (Bang Daus), ecoenzymes, making and the use of organic fertilizers, as well as the development of a waste bank.